Hydrogeochemistry properties of thermal waters and health risk assessment in Şırnak geothermal fields (Turkey) - Davraz, Aysen; Nalbantcilar, M. Tahir; Istin, Aysen Ercan; Kadirhan, Gokhan; Celik, Sedat (Springer, 2025)
Anatolia, one of the most seismically active regions in the world, has very high geothermal potential due to its geological and tectonic structure. Southeastern Anatolia is one of the least studied areas in terms of geothermal potential research. In this region, the geothermal resource inventory and detailed hydrogeochemical properties of the geothermal areas in the G & uuml;& ccedil;l & uuml;konak, Kum & ccedil;at & imath; (& Idot;kizce), Balveren-Besta, and Beyt & uuml;& scedil;& scedil;ebap-Il & imath;cak locations in & Scedil;& imath;rnak province were investigated. The geothermal system in the province is tectonically controlled, with carbonate rocks of various ages constituting the reservoir rocks of the geothermal system. Marl and clayey lithologies serve as cover rocks. The heating sources in geothermal systems are volcanism and the geothermal gradient. The emergence temperature of the geothermal water and EC values of thermal waters with different hydrogeochemical facies (Ca-Mg-HCO3-SO4/Ca-Mg-SO4-HCO3, Na-Ca-Cl-HCO3/Na-Ca-HCO3-Cl) in the province range between 20.8 and 63 degrees C and 756-2095 mu S/cm, respectively. It was determined that the hydrogeochemical structure of thermal waters is controlled by rock-water interaction processes, with silicate weathering, dissolution of evaporite minerals, and cation exchange processes playing significant roles. In the study, health risk assessments were conducted for As, B, Al, and F parameters detected at high levels in thermal water samples. It was found that As may cause cancer in children with long-term oral exposure. In adults, cancer risk is possible with dermal exposure. In the balneological evaluations of thermal waters, it was concluded that all geothermal waters could be used for bathing cures. However, precautions should be taken regarding the bacterial content of the waters for use as drinking cures, and caution should be exercised for long-term use due to the high fluoride and arsenic content. The data obtained in this study serve as fundamental information for increasing the tourism potential of the region.
Keywords: Geothermal fluids; Hydrogeochemistry; Health risk; Arsenic; Tourism